(untitled) (Nigerian Journal of Physiological Sciences, 2019)
Blighia unijugata (Sapindaceae) is an indigenous tree belonging to the tropical forests of West Africa. It is called “Ako Isin” by the Yoruba people of Southern-Western part of Nigeria, where it is among plants used traditionally in the management of depressive psychosis. The aim of this present study was to evaluate the anti-depressant activity of ethanol extract of Blighia unijugata leaves in-vivo using acute and chronic experimental models of depression. The antidepressant activity of ethanol extract of B. unijugata leaves was investigated using acute and chronic unpredictable mild stress. Depression tests used included forced swimming, tail suspension, yohimbine induced lethality and reserpine induced depression tests. Oxidative stress markers were also assessed in the brain homogenates after chronic unpredictable mild stress. The LD50 via oral route of administration was 1414 mg/kg. The results showed that, B. unijugata produced significant reduction in immobility time in forced swimming and tail suspension tests without stimulating in locomotor activity in open field test. It was also found that B. unijugata significantly reversed diarrhea, ptosis and hypothermia in reserpine model of depression. 2.5 mg/kg B. unijugata potentiated yohimbine induced lethality in mice and also reduced the oxidative stress markers. The ethanol extract of B. unijugata leaves possessed antidepressant action, thus justifying its use in the management of mental illness.